Red Blood Cell Transfusion in Pediatric Orthotopic Liver Transplantation: What a Difference a Few Decades Make. (October 2019) - Tran, Lieu T.; Mazariegos, George V.; Damian, Daniela; Davis, Peter J.
Abstract : BACKGROUND: Liver transplantation in children is often associated with coagulopathy and significant blood loss. Available data are limited. In this observational retrospective study, we assessed transfusion practices in pediatric patients undergoing liver transplantation at a single institution over the course of 9 years. METHODS: Data were retrospectively collected from patient medical records at the Children's Hospital of Pittsburgh of University of Pittsburgh Medical Center. All patients who underwent liver transplantation from January 2008 to June 2017 were included. Primary and secondary outcomes were volume of red blood cells (RBCs) transfused and mortality, respectively. RESULTS: From January 2008 to June 2017, there were 278 liver transplants in 271 patients. The number of primary transplants were 259, second retransplants 15, and third retransplants 4. Average age at transplantation was 6.9 years. Biliary atresia, maple syrup urine disease, urea cycle defect, and liver tumor were the leading indications accounting for 66 (23.7%), 45 (16.2%), 24 (8.6%), and 23 (8.3%) of transplants, respectively. Seventy-six cases (27.3%) did not require RBC transfusions. Among those transfused, 181 (89.6%) of the cases required <1 blood volume (BV). The median BV transfused among all cases was 0.21 (range, 0–9; Q1, 0; Q3, 0.45). There is a trend toward higher volume transfusions among infants (median, 0.46 BV) compared to children >12 months of age (0.12 BV). By diagnosis, the group requiring the highest median volume transfusion was patients with total parenteral nutrition–related liver failure (3.41 BV) followed by patients undergoing repeat transplants (0.6 BV). Comparison of primary versus repeat transplants shows a trend toward higher volume transfusions in third transplants (median, 2.71 BV), compared to second transplants (0.43 BV) and primary transplants (0.18 BV). Four of 271 patients (1.5%) died during admission involving liver transplantation. Nine of 271 patients (3.3%) died subsequently. Total mortality was 4.8%. CONCLUSIONS: In contrast to historically reported trends, evaluation of current transfusion practices reveals that most patients undergoing liver transplantation receive <1 BV of packed RBCs. More than 1 in 4 transplantations require no transfusion at all. Risk factors for greater transfusion need include younger age, total parenteral nutrition–related liver failure, and repeat transplantation.